The influence of the form of condensation nucleus on the formation and propagation of acid precipitation near operating TPS; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 82 : Thermophysical Basis of Energy Technologies - Gvozdyakov D. V. Dmitry Vasilievich (2015, 2015)
Title screen